Russian students: work and health - L. . Ivanova (Высшее образование в России)
The article analyzes the data of sociological research «Health of Students» aimed at the ascertainment of the influence of secondary employment on the health of internal officeuniversity students. It is shown that the rate of exhaustion and emotional stress of work depends on gender, self-appraisal of health and aim at its care.